A pole piece and a method for preparing the same

Through dry mixing and stamping forming technology, the traditional current collector support is abolished and the metal wire is directly used for self-support, which solves the problems of long-term production of traditional pole pieces, high energy consumption and waste of materials, and achieves high-efficiency and low-cost pole pieces Production.

CN118610388BActive Publication Date: 2024-12-20JIANGSU TIANHE ENERGY STORAGE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410637085.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2024-12-20
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The traditional electrode sheet manufacturing process takes a long time, high energy consumption, and uses a large amount of copper and aluminum foil substrates, which cannot achieve material cost control and weight reduction.

Method used

The active substance powder, binder, conductive agent and metal wire are mixed by dry mixing method, and the solvent is added to form a viscous slurry. The wet electrode sheet is obtained by stamping and molding, and then dried and pressed to the target thickness, which eliminates the traditional current collector. Support, use wire directly for self-support.

Benefits of technology

The electrode sheet production process has been greatly reduced, the solvent usage and energy consumption have been reduced, the metal usage has been significantly reduced, the production efficiency and material utilization have been improved, and the self-support and good conductivity of the electrode sheet have been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118610388B_ABST
    Figure CN118610388B_ABST
Patent Text Reader

Abstract

The present invention provides a pole piece and a preparation method thereof, specifically, comprising the following steps: (1) dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture; (2) adding a solvent to the solid material mixture and stirring to obtain a viscous slurry; (3) stamping the viscous slurry and a sheet metal pole ear to obtain a wet pole piece; (4) drying the solvent in the wet pole piece to obtain a dry pole piece; (5) pressing the dry pole piece to a thickness of 0.05-5 mm to obtain a pole piece; the diameter of the metal wire is 1-10 μm, the aspect ratio of the metal wire is 1000-8000, and the roughness of the metal wire is 0.5-8 μm. The method of the present invention uses a metal wire with a certain roughness and selects a metal wire with a suitable diameter and aspect ratio, which can reduce the interfacial tension between the metal wire and the slurry, improve the adhesion between the two materials, and prevent the pole piece from cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials, and specifically relates to a pole piece and a preparation method thereof. Background Art

[0002] Pole sheet design and manufacturing are key processes in the production of lithium batteries. The traditional pole sheet manufacturing process involves slurrying, coating, cold pressing and other processes. The formed pole sheet contains a copper-aluminum foil substrate and an active material membrane layer. The traditional pole sheet manufacturing process is time-consuming and energy-intensive, and a large amount of copper-aluminum foil substrate is used in pole sheet forming. According to calculations, the mass proportion of copper foil in the negative electrode sheet is 20%-30%, and the mass proportion of aluminum foil in the positive electrode sheet is 8%-15%. Therefore, streamlining the pole sheet manufacturing process and reducing the use of copper-aluminum substrates are the main directions for optimizing current pole sheet manufacturing.

[0003] Traditional electrode manufacturing involves mixing the active materials evenly using a wet method and then coating them on the current collector to prepare a 50-200μm thick electrode, which is then cold pressed and die-cut to obtain the final electrode. This preparation method involves many processes and is time-consuming. At the same time, a large amount of solvent is consumed in the slurry process, and the coating process also requires high energy consumption to dry and volatilize the solvent in the electrode.

[0004] 24M, founded by MIT materials science professor Jiang Yeming, has developed a thick electrode technology that greatly increases the thickness of the electrode through process innovation. Compared with the existing technology, the electrode thickness is increased by 5 times, and 80% of the current collector support is abandoned. See US 61 / 736,798. Tesla's dry electrode technology evenly mixes the active material, conductive agent and binder, and then directly extrude the electrode membrane through high temperature and high pressure, and then composites it with the current collector. 24M's preparation of thick electrodes in the form of current collector + active material membrane will greatly deteriorate the electronic and ion conductivity of the electrode. The polarization impedance of the battery made with thick electrodes will be very large, and it cannot be charged and discharged at normal current density. Although the dry electrode technology eliminates the slurry process and avoids solvent consumption, it still consumes a lot of electricity in the high temperature and high pressure of the membrane extrusion molding process, and die-cutting and stripping are required for the final molding of the electrode. Both 24M's thick electrode technology and Tesla's dry electrode technology use the traditional pole piece structure. A large amount of copper and aluminum foil substrate will be used in the pole piece manufacturing process, which cannot effectively reduce weight and control material costs. Summary of the invention

[0005] The object of the present invention is to provide a pole piece and a preparation method thereof which are simple to manufacture, have reduced production costs and high production efficiency.

[0006] A first aspect of the present invention provides a method for preparing a pole piece, comprising the following steps:

[0007] (1) dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture;

[0008] (2) adding a solvent to the solid matter mixture and stirring to obtain a viscous slurry;

[0009] (3) stamping the viscous slurry and the sheet-shaped metal tab to obtain a wet electrode;

[0010] (4) drying the solvent in the wet electrode to obtain a dry electrode;

[0011] (5) Pressing the dry electrode sheet to a thickness of 0.05-5 mm to obtain the electrode sheet;

[0012] The diameter of the metal wire is 1-10 μm, the aspect ratio of the metal wire is 1000-8000, and the roughness of the metal wire is 0.5-8 μm.

[0013] In one or more embodiments, the diameter of the metal wire is 1-9 μm, and / or the roughness of the metal wire is 0.5-7 μm.

[0014] In one or more embodiments, the diameter of the metal wire is 3-6 μm, the aspect ratio of the metal wire is 3000-8000, and the roughness of the metal wire is 0.5-5 μm; or the diameter of the metal wire is 4-8 μm, the aspect ratio of the metal wire is 1000-5000, and the roughness of the metal wire is 1-5 μm.

[0015] In one or more embodiments, the method has one or more of the following features:

[0016] The binder is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose and styrene-butadiene rubber;

[0017] The solvent is N-methylpyrrolidone or water;

[0018] The active material powder is lithium iron phosphate or graphite;

[0019] The conductive agent is conductive carbon black;

[0020] The metal wire is an aluminum wire or a copper wire.

[0021] In one or more embodiments, the mass fraction of the metal wire in the solid matter mixture is 3%-15%.

[0022] In one or more embodiments, in the solid material mixture, the mass fractions of the active material powder, the binder and the conductive agent are 80%-95%, 0.5%-5% and 0.5%-5%, respectively.

[0023] In one or more embodiments, in step (1), lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and aluminum wire are mixed into a solid material mixture, in which the mass fractions of lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and aluminum wire are 89%-93%, 1%-3%, 1%-3% and 3%-9%, respectively; the diameter of the aluminum wire is 3-6 μm, the aspect ratio of the aluminum wire is 3000-8000, and the roughness of the aluminum wire is 0.5-4 μm.

[0024] In one or more embodiments, in step (1), graphite, sodium carboxymethyl cellulose, conductive carbon black, styrene-butadiene rubber and copper wire are mixed into a solid material mixture, in which the mass fractions of graphite, sodium carboxymethyl cellulose, conductive carbon black, styrene-butadiene rubber and copper wire are 82%-90%, 0.5%-2%, 0.5%-2%, 0.5%-2% and 5%-15%, respectively; the diameter of the copper wire is 4-8 μm, the aspect ratio of the copper wire is 1000-5000, and the roughness of the copper wire is 1-5 μm.

[0025] In one or more embodiments, in step (2), the mass fraction of the solvent is >0% and ≤15%, based on the total mass of the viscous slurry.

[0026] In one or more embodiments, step (3) comprises: laying two or more layers of the viscous slurry in a mold, placing a sheet metal tab between two adjacent layers of the viscous slurry, and ensuring that the thickness of the two adjacent layers of the viscous slurry is the same.

[0027] The second aspect of the present invention provides a pole piece prepared using the method described in the first aspect of the present invention.

[0028] A third aspect of the present invention provides an electrochemical device, wherein the electrochemical device comprises the electrode piece described in the second aspect of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the mixing process of the viscous slurry in some embodiments of the present invention, wherein ① is a metal wire; ② is an active material powder; ③ is a binder; ④ is a conductive agent; ⑤ is a solvent; and ⑥ is a viscous slurry.

[0030] Figure 2 It is a schematic diagram of one-step forming of a pole piece in some embodiments of the present invention, wherein ⑥ is a viscous slurry; ⑦ is a pole piece. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0032] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0033] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0034] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0035] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0036] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0037] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0038] The present invention provides a method for preparing a pole piece, comprising the following steps:

[0039] (1) dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture;

[0040] (2) adding a solvent to the solid matter mixture and stirring to obtain a viscous slurry;

[0041] (3) stamping the viscous slurry and the sheet-shaped metal tabs to obtain wet electrode sheets;

[0042] (4) drying the solvent in the wet electrode to obtain a dry electrode;

[0043] (5) Press the dry electrode to a thickness of 0.05-5 mm to obtain the electrode.

[0044] The binder may be selected from one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR). In some embodiments, the binder is polyvinylidene fluoride. In some embodiments, the binder is carboxymethyl cellulose and styrene butadiene rubber. The solvent may be N-methyl pyrrolidone (NMP) or water. The active material powder may be lithium iron phosphate or graphite. The solvent and the binder may be selected according to the properties of the active material powder. In some embodiments, the active material powder is lithium iron phosphate; the solvent is NMP; the binder is polyvinylidene fluoride. In some embodiments, the active material powder is graphite; the solvent is water; the binder is carboxymethyl cellulose and styrene butadiene rubber. The conductive agent may be conductive carbon black (SP).

[0045] The metal of the metal wire is a metal with certain strength and conductivity. Preferably, the metal wire is an aluminum wire or a copper wire.

[0046] In the present invention, the diameter of the metal wire is 1-10 μm, the aspect ratio of the metal wire is 1000-8000, and the roughness of the metal wire is 0.5-8 μm. Controlling the diameter, aspect ratio, and roughness of the metal wire within the aforementioned range is beneficial to improving the supporting effect of the metal wire in the pole piece and the conductive performance of the pole piece, and is beneficial to preventing the pole piece from cracking.

[0047] The diameter of the metal wire may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm. Preferably, the diameter of the metal wire is 1-9 μm, 2-9 μm, 1-8 μm, 3-8 μm, 3-6 μm, 4-8 μm. The aspect ratio of the metal wire may be 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000. Preferably, the aspect ratio of the metal wire is 1000-7000, 1000-6000, 1000-5000, 2000-8000, 3000-5000, 3000-8000. The roughness of the metal wire may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm. Preferably, the roughness of the metal wire is 0.5-7 μm, 0.5-6 μm, 0.5-5 μm, 0.5-4 μm, 0.5-2 μm, 1-7 μm, 1-6 μm, 1-5 μm, 1-3 μm, 2-4 μm, 3-5 μm. In some embodiments, the diameter of the metal wire is 1-9 μm, and the roughness of the metal wire is 0.5-7 μm. In some embodiments, the diameter of the metal wire is 1-8 μm, the aspect ratio of the metal wire is 1000-8000, and the roughness of the metal wire is 0.5-8 μm. In some embodiments, the diameter of the metal wire is 3-6 μm, the aspect ratio of the metal wire is 3000-8000, and the roughness of the metal wire is 0.5-5 μm. In other embodiments, the diameter of the metal wire is 4-8 μm, the aspect ratio of the metal wire is 1000-5000, and the roughness of the metal wire is 1-5 μm.

[0048] The present invention eliminates the traditional current collector (such as copper and aluminum foil) used for supporting and conducting the pole piece, and directly adds metal wires of different lengths (such as copper wires or aluminum wires) to the active material powder, binder and conductive agent for mixing, and then makes a viscous slurry. The pole piece prepared using this viscous slurry, because it is rich in metal wires inside, is similar to a reinforced concrete structure, and can play a good role in supporting and fixing the powder, thereby achieving self-support of the pole piece. The pole piece using this structure can greatly reduce the use of metal (such as copper and aluminum). It is estimated that the mass fraction of copper metal in the negative electrode can be reduced to less than 10%, and the mass fraction of aluminum metal in the positive electrode can be reduced to less than 5%. Adding metal wires that meet the above conditions to the viscous slurry can produce a good supporting effect on the pole piece, and the pole piece has good conductive properties.

[0049] In step (1), in the solid material mixture, the mass fraction of the metal wire ① can be 3%-15%, such as 5%-12%, 8%-10%, 6%-11% or 7%-9%. The mass fraction of the active material powder ② can be 80%-95%, such as 82%-92%, 85%-88%. The mass fraction of the binder ③ can be 0.5%-5%, such as 1%-4% or 2%-3%. The mass fraction of the conductive agent ④ can be 0.5%-5%, such as 1%-4% or 2%-3%. In some embodiments, in step (1), the active material powder is lithium iron phosphate, the binder is PVDF, the conductive agent is SP, and the metal wire is aluminum wire. In the solid material mixture, the mass fractions of lithium iron phosphate, PVDF, SP and aluminum wire are 89%-93%, 1%-3%, 1%-3% and 3%-9%, respectively. Preferably, in the solid material mixture, the mass fractions of lithium iron phosphate, PVDF, SP and aluminum wire are 90%-92%, 1.5%-2.5%, 1.5%-2.5% and 4%-7%, respectively. The mass fraction of aluminum wire is preferably 2%-6%. Preferably, the diameter of the aluminum wire is 3-6 μm, the aspect ratio of the aluminum wire is 3000-8000, and the roughness of the aluminum wire is 0.5-4 μm. In some embodiments, the active material powder is graphite, the binder is CMC and SBR, the conductive agent is SP, the metal wire is copper wire, and in the solid material mixture, the mass fractions of graphite, CMC, SP, SBR, and copper wire are 82%-90%, 0.5%-2%, 0.5%-2%, 0.5%-2% and 5%-15%, respectively. Preferably, the mass fractions of graphite, CMC, SP, SBR and copper wire are 85%-88%, 1%-1.5%, 1%-1.5%, 1%-1.5% and 5%-15% respectively. The mass fraction of copper wire is preferably 6%-13%. Preferably, the diameter of the copper wire is 4-8 μm, the aspect ratio of the copper wire is 1000-5000, and the roughness of the copper wire is 1-5 μm.

[0050] In step (2), the mass fraction of solvent ⑤ is greater than 0% and less than or equal to 15%, based on the total mass of viscous slurry ⑥. Preferably, the mass fraction of the solvent in the viscous slurry is 0.1%-15%, for example, 0.5%, 2%, 5%, 8%, 10%, 12%. Different from the traditional slurry mixing, the present invention proposes a new mixing method: first, the solid substances are dry-mixed, and then a small amount of solvent is added to the mixed solid substance mixture, and it is mixed into a viscous slurry in a manner similar to kneading dough to obtain an ultra-high solid content viscous slurry. The use of the obtained ultra-high solid content viscous slurry to prepare electrodes can greatly reduce the use of solvents.

[0051] In step (3), two or more layers of viscous slurry can be laid flat in the mold, for example, three, four, five, six or more layers of viscous slurry are laid flat. A sheet metal pole ear is placed between two adjacent layers of viscous slurry. The material of the metal pole ear can be copper, aluminum or nickel. The thickness of the two adjacent layers of viscous slurry should be the same. The number of layers and thickness of the viscous slurry can be determined according to the thickness of the ultra-thick pole piece to be prepared. In some embodiments, if a pole piece with a thickness of 1.5 mm is to be prepared, the total thickness of each layer of the viscous slurry should be ≥1.6 mm. In some embodiments, if a pole piece with a thickness of 0.75 mm is to be prepared, the total thickness of each layer of the viscous slurry should be ≥0.8 mm.

[0052] The ultra-high solid content viscous slurry proposed in the present invention can realize one-step stamping of the pole piece. At the same time, the viscous slurry can greatly reduce energy consumption and shorten time during the drying process due to less solvent.

[0053] The present invention also provides a pole piece ⑦ prepared by the method of the present invention. The thickness of the pole piece is between 0.05-5 mm, such as 0.1 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm. The compacted density of the pole piece of the present invention is 1-3 g / cc, such as 1.5 g / cc, 2 g / cc, 2.5 g / cc. The pole piece prepared by the method of the present invention can be applied to lithium ion batteries, sodium ion batteries and other electrochemical devices requiring electrode structures.

[0054] The present invention has the following beneficial effects:

[0055] (1) The method of the present invention greatly reduces the production process and directly realizes the electrode production by homogenization and one-step stamping, which greatly reduces the electrode production process and improves production efficiency.

[0056] (2) The method of the present invention uses an ultra-high solid content viscous slurry, which can realize one-step stamping of the electrode, reduce the amount of solvent used, reduce solvent costs, and facilitate drying to reduce energy consumption.

[0057] (3) The method of the present invention eliminates the copper-aluminum foil support and current collection in the traditional pole piece, and directly adds the metal wire to the slurry for mixing to achieve self-support and current collection of the pole piece, which can significantly reduce the amount of metal (such as copper or aluminum) used in the pole piece, save materials, and reduce costs.

[0058] (4) The one-dimensional structural characteristics of the metal wire in the method of the present invention avoid the barrier effect of the copper-aluminum foil current collector in the traditional electrode plate on the electrolyte infiltration and transmission, shortening the electrolyte infiltration time and the transmission path of the electrolyte replenishment during the cycle.

[0059] (5) The method of the present invention roughens the surface of the metal wire and selects a metal wire with a suitable diameter and aspect ratio, which can reduce the interfacial tension between the metal wire and the slurry, improve the adhesion between the two materials, and prevent the electrode from cracking.

[0060] (6) The method of the present invention can realize the manufacture of ultra-thick electrode sheets with a thickness range of up to 50-5000um.

[0061] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by weight.

[0062] In the present invention, the method for measuring compacted density is as follows:

[0063] Compacted density = (pole piece weight - substrate weight) / (sampling area*(pole piece thickness - substrate thickness)).

[0064] In the present invention, metal wire is used to replace the current collector in the traditional process. When testing the compaction density of the pole pieces obtained in Examples 1-2 of the present invention, the weight of the substrate is the total weight of the metal wire used in preparing the pole pieces, the thickness of the substrate = the volume of the metal wire / sampling area, and the volume of the metal wire = the total weight of the metal wire / the density of the metal wire.

[0065] In the present invention, the aspect ratio of the metal wire refers to the ratio of the length to the diameter of each metal wire in the viscous slurry. The length and diameter of the metal wire are measured using conventional methods in the art.

[0066] In the present invention, the method for measuring the roughness of the metal wire is: referring to GB / T 7220-2004 "Surface structure profile method surface roughness terminology parameter measurement", and using an electric profiler device for testing. The electric profiler device has a testing capability range of 0.02-150 μm.

[0067] In the present invention, the purchased metal wire is roughened. Since the surface of the metal wire is easily oxidized, it should be used in a short time after the roughening treatment. The method for roughening the metal wire is as follows:

[0068] Copper wire: (1) Soak in concentrated sulfuric acid (concentration: 10-14 mol / L) for 10-120 min. The longer the soaking time, the greater the roughness. The appropriate soaking time can be selected as needed; (2) Then wash with deionized water to obtain copper wires with different roughness. Aluminum wire: (1) Soak in dilute hydrochloric acid (concentration: 2-8 mol / L) for 10-120 min. The longer the soaking time, the greater the roughness. The appropriate soaking time can be selected as needed; (2) Then wash with deionized water to obtain copper wires with different roughness.

[0069] Example 1: Preparation of lithium iron phosphate pole piece

[0070] Lithium iron phosphate, PVDF, SP and aluminum wire are dry-mixed in a mass ratio of 91.5:1.9:1.6:5. The diameter of the aluminum wire is 3-6 μm, and the aspect ratio of the aluminum wire is 3000-8000. The aluminum wire is soaked in a hydrochloric acid solution for 30 minutes and then washed with deionized water. The roughness Ra of the obtained aluminum wire is 0.5-4 μm.

[0071] The above solid materials are dry-mixed in proportion, and after being mixed evenly, NMP solvent is added, wherein the mass ratio of the solvent to the solid material is 1:9. After the solvent is added, knead and stir until it becomes viscous, and the dry powder in the solid-liquid mixture is all wetted, at which point it can be determined that the solid-liquid mixture is evenly mixed.

[0072] Spread the mixed viscous slurry flat in the mold, place the sheet metal Al pole ear on the flat viscous slurry, and then spread another layer of slurry to ensure that the thickness of the upper and lower layers of slurry are consistent. The thickness of each layer of slurry is at least 0.8mm. Finally, stamp it into shape to obtain a wet pole piece.

[0073] After stamping, the solvent in the wet electrode is dried to obtain a dry electrode, and finally the dry electrode is placed in a specific mold and pressed to a thickness of 1.5 mm.

[0074] The compacted density of the pole piece of Example 1 was measured to be 2.5 g / cc.

[0075] Example 2: Preparation of graphite pole piece

[0076] Graphite, CMC, SP, SBR and copper wire are dry-mixed in a mass ratio of 86:1.35:1.35:1.3:10. The diameter of the copper wire is 4-8 μm, and the aspect ratio of the copper wire is 1000-5000. The copper wire is soaked in a concentrated sulfuric acid solution for 30 minutes and then washed with deionized water. The roughness Ra of the obtained copper wire is 1-5 μm.

[0077] The above solid substances are dry-mixed in proportion, and distilled water is added after mixing evenly, wherein the mass ratio of solvent to solid substance is 1:9. After the solvent is added, knead and stir until it becomes viscous, and the dry powder in the solid-liquid mixture is all wetted, at which point it can be determined that the solid-liquid mixture is evenly mixed.

[0078] Spread the mixed viscous slurry flat in the mold, place the sheet metal Cu pole ear on the flat viscous slurry, and then spread another layer of slurry to ensure that the thickness of the upper and lower layers of slurry are consistent. The thickness of the two layers of slurry is at least 0.4mm. Finally, stamp and form to obtain the wet pole piece.

[0079] After stamping, the solvent in the wet electrode is dried to obtain a dry electrode, and finally the dry electrode is placed in a specific mold and pressed to a thickness of 0.75 mm.

[0080] The compacted density of the pole piece of Example 2 was measured to be 1.5 g / cc.

[0081] Example 3: Preparation of lithium iron phosphate pole piece

[0082] The roughness Ra of the aluminum wire is selected to be 2-4 μm, and the remaining steps are consistent with those of Example 1.

[0083] Example 4: Preparation of graphite pole piece

[0084] The roughness Ra of the copper wire is selected to be 3-5 μm, and the remaining steps are consistent with those in Example 2.

[0085] Example 5: Preparation of lithium iron phosphate pole piece

[0086] The roughness Ra of the aluminum wire is selected to be 0.5-2 μm, and the remaining steps are consistent with those of Example 1.

[0087] Example 6: Preparation of lithium iron phosphate pole piece

[0088] The roughness Ra of the aluminum wire is selected to be 1-3 μm, and the remaining steps are consistent with Example 1.

[0089] Comparative Example 1: Preparation of lithium iron phosphate pole piece

[0090] Lithium iron phosphate, PVDF, SP and aluminum wire are dry-mixed in a mass ratio of 91.5:1.9:1.6:5, the diameter of the aluminum wire is 3-6 μm; the aspect ratio of the aluminum wire is 3000-8000; the aluminum wire is soaked in a hydrochloric acid solution for 60 minutes and then washed with deionized water, and the roughness Ra of the obtained aluminum wire is 9-12 μm.

[0091] The above solid materials are dry-mixed in proportion, and after being mixed evenly, NMP solvent is added, wherein the mass ratio of the solvent to the solid material is 1:9. After the solvent is added, knead and stir until it becomes viscous, and the dry powder in the solid-liquid mixture is all wetted, at which point it can be determined that the solid-liquid mixture is evenly mixed.

[0092] Spread the mixed viscous slurry flat in the mold, place the sheet metal Al pole ear on the flat viscous slurry, and then spread another layer of slurry to ensure that the thickness of the upper and lower layers of slurry are consistent. The thickness of each layer of slurry is at least 0.8mm. Finally, stamp it into shape to obtain a wet pole piece.

[0093] After stamping, the solvent in the wet electrode is dried to obtain a dry electrode, and finally the dry electrode is placed in a specific mold and pressed to a thickness of 1.5 mm.

[0094] The compaction density of the pole piece of Comparative Example 1 was measured to be 2.5 g / cc.

[0095] Comparative Example 2: Preparation of lithium iron phosphate pole piece

[0096] The roughness Ra of the aluminum wire is selected to be 0-0.4 μm, and the remaining steps are consistent with those of Example 1.

[0097] Comparative Example 3: Preparation of graphite pole piece

[0098] Graphite, CMC, SP, SBR and copper wire are dry-mixed in a mass ratio of 86:1.35:1.35:1.3:10, the diameter of the copper wire is 4-8 μm; the aspect ratio of the copper wire is 1000-5000; the copper wire is soaked in a concentrated sulfuric acid solution for 50 minutes and then washed with deionized water, and the roughness Ra of the obtained copper wire is 10-15 μm.

[0099] The above solid substances are dry-mixed in proportion, and distilled water is added after mixing evenly, wherein the mass ratio of solvent to solid substance is 1:9. After the solvent is added, knead and stir until it becomes viscous, and the dry powder in the solid-liquid mixture is all wetted, at which point it can be determined that the solid-liquid mixture is evenly mixed.

[0100] Spread the mixed viscous slurry flat in the mold, place the sheet metal Cu pole ear on the flat viscous slurry, and then spread another layer of slurry to ensure that the thickness of the upper and lower layers of slurry are consistent. The thickness of the two layers of slurry is at least 0.4mm. Finally, stamp and form to obtain the wet pole piece.

[0101] After stamping, the solvent in the wet electrode is dried to obtain a dry electrode, and finally the dry electrode is placed in a specific mold and pressed to a thickness of 0.75 mm.

[0102] The compacted density of the electrode of Comparative Example 3 was measured to be 1.5 g / cc.

[0103] Comparative Example 4: Preparation of graphite pole piece

[0104] The roughness Ra of the copper wire is selected to be 0-0.4 μm, and the remaining steps are consistent with those in Example 2.

[0105] Comparative Example 5: Preparation of lithium iron phosphate pole piece

[0106] The diameter of the aluminum wire is selected to be 11-15 μm, and the remaining steps are consistent with Example 1.

[0107] Comparative Example 6: Preparation of lithium iron phosphate pole piece

[0108] The diameter of the aluminum wire is selected to be 16-20 μm, and the remaining steps are consistent with Example 1.

[0109] Comparative Example 7: Preparation of lithium iron phosphate pole piece

[0110] The aspect ratio of the aluminum wire is selected to be 500-900, and the remaining steps are the same as those in Example 1.

[0111] Comparative Example 8: Preparation of lithium iron phosphate pole piece

[0112] The aspect ratio of the aluminum wire is selected to be 9000-15000, and the remaining steps are consistent with those in Example 1.

[0113] Table 1 Experimental results of each scheme

[0114]

[0115]

[0116] After the pole piece is manufactured, the test results are visually judged based on whether the pole piece is cracked or not, and the crack severity is divided into ten levels from 0 to 9, where 0 means no cracking and no abnormality, and 9 means severe cracking and no support.

[0117] From the experimental results of Comparative Examples 1 and 3, the roughness of the metal wire is too large, the structural stability of the metal wire is poor, it is easy to break during the sample preparation process, and it does not play a good supporting role, resulting in serious cracking of the electrode; from the experimental results of Comparative Examples 2 and 4, the roughness of the metal wire is too low, the adhesion between the electrode slurry and the metal wire is low, the supporting effect of the metal wire is poor, and it is slightly cracked; from the experimental results of Comparative Examples 5 and 6, the diameter of the metal wire is too large, the thickness of the metal wire in the vertical direction accounts for a large proportion, which is not conducive to the adhesion between the electrode slurry and the metal wire, resulting in cracking, and as the diameter of the metal wire increases, the degree of cracking worsens; the experimental results of Comparative Examples 7 and 8 show that the aspect ratio of the metal wire also has a certain influence on whether the electrode cracks. If the aspect ratio of the metal wire is too small, the metal wire is well dispersed but the cross-linking effect is poor, so the supporting effect is poor, resulting in slight cracking. If the aspect ratio of the metal wire is too large, the metal wire is not easy to disperse and is easy to agglomerate, and the supporting effect is also poor, resulting in cracking of the electrode.

Claims

1. A method for preparing a pole piece, characterized in that: The following steps are involved: (1) dry-mixing active material powder, a binder, a conductive agent and a metal wire to obtain a solid material mixture; (2) adding a solvent to the solid matter mixture and stirring to obtain a viscous slurry; (3) stamping the viscous slurry and the sheet-shaped metal tab to obtain a wet electrode; (4) drying the solvent in the wet electrode to obtain a dry electrode; (5) Pressing the dry electrode sheet to a thickness of 0.05-5 mm to obtain the electrode sheet; The metal wire is an aluminum wire or a copper wire, the diameter of the metal wire is 1-10 μm, the aspect ratio of the metal wire is 1000-8000, and the roughness of the metal wire is 0.5-8 μm.

2. The preparation method according to claim 1, characterized in that The diameter of the metal wire is 1-9 µm, and / or the roughness of the metal wire is 0.5-7 µm.

3. The preparation method according to claim 1, characterized in that: The diameter of the metal wire is 3-6µm, the aspect ratio of the metal wire is 3000-8000, and the roughness of the metal wire is 0.5-5µm; or the diameter of the metal wire is 4-8µm, the aspect ratio of the metal wire is 1000-5000, and the roughness of the metal wire is 1-5µm.

4. The preparation method according to claim 1, characterized in that: The method has one or more of the following features: The binder is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose and styrene-butadiene rubber; The solvent is N-methylpyrrolidone or water; The active material powder is lithium iron phosphate or graphite; The conductive agent is conductive carbon black.

5. The preparation method according to claim 1, characterized in that: In the solid matter mixture, the mass fraction of the metal wire is 3%-15%.

6. The preparation method according to claim 1, characterized in that: In the solid material mixture, the mass fractions of the active material powder, the binder and the conductive agent are 80%-95%, 0.5%-5% and 0.5%-5% respectively.

7. The preparation method according to claim 1, characterized in that In step (1), lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and aluminum wire are mixed into a solid material mixture, wherein the mass fractions of lithium iron phosphate, polyvinylidene fluoride, conductive carbon black and aluminum wire are 89%-93%, 1%-3%, 1%-3% and 3%-9% respectively; the diameter of the aluminum wire is 3-6µm, the aspect ratio of the aluminum wire is 3000-8000, and the roughness of the aluminum wire is 0.5-4µm; or In step (1), graphite, sodium carboxymethyl cellulose, conductive carbon black, styrene-butadiene rubber and copper wire are mixed into a solid material mixture, wherein the mass fractions of graphite, sodium carboxymethyl cellulose, conductive carbon black, styrene-butadiene rubber and copper wire are 82%-90%, 0.5%-2%, 0.5%-2%, 0.5%-2% and 5%-15% respectively; the diameter of the copper wire is 4-8µm, the aspect ratio of the copper wire is 1000-5000, and the roughness of the copper wire is 1-5µm.

8. The preparation method according to claim 1, characterized in that: In step (2), the mass fraction of the solvent is greater than 0% and less than or equal to 15%, based on the total mass of the viscous slurry.

9. The preparation method according to claim 1, characterized in that: Step (3) comprises: laying two or more layers of the viscous slurry in a mold, placing a sheet metal tab between two adjacent layers of the viscous slurry, and ensuring that the thickness of the two adjacent layers of the viscous slurry is the same.

10. A pole piece prepared by the method according to any one of claims 1 to 9.

11. An electrochemical device, characterized in that: The electrochemical device comprises the electrode piece according to claim 10.